ANALISIS KENDALA-KENDALA POTENSIAL PENERAPAN TOTAL QUALITY SERVICE PADA PERGURUAN TINGGI - Nursya’bani Purnama (Faculty of Economics and Business, Universitas Gadjah Mada, 2002)
The succes of Higher Educational Institution in competing is highly depends on how the institution gives the satisfaction to customers through the creation of quality service. Many corporations have got their success because they are able to apply quality management principles. Total Quality Service (TQS) is a service quality management that can be used as strategic tools for Higher Educational Institution in the effort to get sustainable service quality improvement. In order to apply the TQS successfully, a Higher Educational Institution must be able to identify existing constraints.This research is intended to find potential constraints on the application of TQS and it was conducted in the Private University, School of Business, and Academy of Management/Accounting in Yogyakarta. This research is also to test the differences of potential constraints on the application of TQS among the Higher Education, that is Private University, School of Business, and Academy of Management/Accounting. Instruments used in this research are the same as the research instruments used by the previous research conducted by Ngai and Cheng (1999). The respondents of this research are faculties who have structural position in the Faculty of Economics in Private University, School of Business, and Academy of Management/Accounting.This research findings show that, in general, the potential constaints on the application of TQS in the Higher Education are cultural and employee factor, infrastructural factor, and organizational factor. Other findings also show that infrastructural factor is the main constraint, and is followed by cultural and employee factor, and organizational factor. By using a hypothetical testing with 95% confidence level, the conclusions of the findings are follow: there are no significant differences of the potential constraints on the application of TQS in the higher education; there are no significant differences of the potential constraint on the application of TQS between Private University and School of Business; and there are significant differences of the potential constraint on the application of TQS between Private University and Academy of Management/Accounting, and School of Business with Academy of Management/ Accounting.Keywords: potential constraints, Total Quality Service, service quality, customer